Severe acute respiratory syndrome coronavirus 2 vaccine breakthrough infections: A single metro-based testing network experience - Strickler, Samantha S.; Esper, Annette; Wells, Leona; Wood, Anna; Frediani, Jennifer K.; Nehl, Eric; Waggoner, Jesse J.; Rebolledo, Paulina A.; Levy, Joshua M.; Figueroa, Janet; Ramachandra, Thanuja; Lam, Wilbur; et al. (Frontiers in Medicine, 2022)
Objectives: Understanding the incidence and characteristics that influence severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine breakthrough infections (VBIs) is imperative for developing public health policies to mitigate the COVID-19 pandemic. We examined these factors and post-vaccination mitigation practices in individuals partially and fully vaccinated against SARS-CoV-2. Methods: Adults > 18 years old were voluntarily enrolled from a single metro-based SARS-CoV-2 testing network from January to July 2021. Participants were categorized as asymptomatic or symptomatic, and as unvaccinated, partially vaccinated, or fully vaccinated. All participants had confirmed SARS-CoV-2 infection based on standard of care testing with nasopharyngeal swabs. Variant analysis by rRT-PCR was performed in a subset of time-matched vaccinated and unvaccinated individuals. Results: Participants (n=1,317) voluntarily underwent testing for SARS-CoV-2 during the enrollment period. 29.5% of the population received at least one SARS-CoV-2 vaccine (n=389), 12.8% partially vaccinated (n=169); 16.1% fully vaccinated (n=213)). 21.3 % of partially vaccinated individuals tested positive (n=36) and 9.4% of fully vaccinated individuals tested positive (n=20) for SARS-CoV-2. Pfizer/BioNTech mRNA-1273 was the predominant vaccine received (1st dose = 66.8%, 2nd dose = 67.9%). Chronic liver disease and immunosuppression were more prevalent in the vaccinated (partially/fully) group compared to the unvaccinated group (p =0.003, p = 0.021 respectively). There were more asymptomatic individuals in the vaccinated group compared to the unvaccinated group (n= 6 (10.7%), n= 16 (4.1%), p=0.045). CT values were lower for the unvaccinated group (median 24.3, IQR 19.1-30.5) compared to the vaccinated group (29.4, 22.0-33.7, p = 0.004). In the vaccinated group (n= 56), 18 participants were successfully contacted, 7 were lost to follow-up, and 2 were deceased. 50% (n=9) required hospitalization due to COVID-19 illness. Adherence to nationally endorsed mitigation strategies varied post-vaccination. Conclusion: The incidence of SARS-CoV-2 infection at this center was 21.3% in the partially vaccinated group and 9.4% in the fully vaccinated group. Chronic liver disease and immunosuppression were more prevalent in the vaccinated SARS-CoV-2 positive group, suggesting that these may be risk factors for VBIs. Partially and fully vaccinated individuals had a higher incidence of asymptomatic SARS-CoV-2 and higher CT values compared to unvaccinated SARS-CoV-2 positive individuals.